Pathways toward Water Sensitive Cities: An Educational Approach through Geography Learning - Faiz Urfan; Riko Arrasyid (Jurnal Pendidikan Ilmu Sosial, 2023)
The 2030 Sustainable Development Goals (SDGs) have seventeen global goals for the sustainability of human life on planet Earth. One of these goals is to ensure access to water and sanitation for all. This article aims to formulate a grand design of Geography learning as part of social studies taught in the school. The context of the research is the east coast of Aceh Province. The research method used in this paper is a systematic literature review through books, scientific journals, and reports from several community-based water development programs. The grand design is formulated within ten years with three phases, namely (1) Acceleration; (2) Evaluation, and (3) Sustainable Education. The results of this literature review are expected to contribute to the management of water resources in the coastal area of East Aceh while at the same time increasing the implementation of the Merdeka Belajar (Independence Learning) policy at every level of education that is oriented toward local natural resources.